Keys to new market entry strategy to Japan: Case: Portuguese footwear - Palmu, Jonna Maarit (2020)
Japan is the second largest retail market and third biggest importer of footwear in the world. Owning limited domestic manufacturing but being included in the top 6 countries in the world for footwear consumption with high purchasing power per capita, makes Japan a tempting market for the Portuguese footwear cluster to obtain. The Portuguese footwear industry has been in rapid growth during the past decade and today it exports more than 95 % of its manufacturing. APICCAPS is a nationwide association in Portugal that supports the globalization plans of its members from the footwear industry. On the global market, Portuguese footwear presents itself as a young, sexy and forward looking industry which combines tradition with cutting-edge technologies and know-how of greatest design. This appears as a strong competitive advantage in Japan. In addition to exigent quality expectations, modern Japanese consumers are driven by strong individualization and appealing brand stories. Japan is a challenging but highly profitable market due to its vibrant economy and social patterns. The objective of this project is to reveal the key factors and decision points to a successful market entry strategy in Japan, to act as a guideline for the Portuguese footwear companies.